Escitalopram oxalate-loaded chitosan nanoparticle in situ gel formulation intended for direct nose-to-brain delivery: in vitro, ex vivo, and in vivo pharmacokinetic evaluation - Mujtaba, Md Ali; Rashid, Md Abdur; Godbole, Mangesh D.; Alhamhoom, Yahya; Shende, Divyashri S.; Alshehri, Sameer; Akbar, Mohammad J.; Kaleem, Mohammed; Mahajan, Ujwala N.; Shahzad, Naiyer (Frontiers in Pharmacology, 2025)
Introduction: Escitalopram oxalate (ESCI) is a biopharmaceutical classification system (BCS) class II antidepressant drug, that suffers limited oral bioavailability due to extensive hepatic metabolism. Therefore, this study aimed to develop and evaluate chitosan nanoparticles (CSNPs) embedded in an in situ gel for intranasal (i.n) drug delivery.Methods: ESCl-loaded CSNPs were prepared by the ionic gelation method and were optimized using 32 factorial design. The optimized CSNPs were incorporated into pH-sensitive in situ gel composed of carbopol 940 and HPMC K4M for i. n administration.Results: The optimized CSNPs exhibited a particle size of 189 ± 3.14 nm, polydispersity index 0.372 ± 0.84, zeta potential 22.2 ± 1.25 mV, and entrapment efficiency of 76.5% ± 1.64%. FTIR, DSC, and XRD analysis of CSNPs confirmed the encapsulation of the ESCI within the formulation. The in vitro drug release profile of the ESCI-loaded CSNPs in situ gel exhibited an initial burst release followed by a slow and sustained release phase. The in situ gel studies demonstrated that 80.72% ± 3.12% of the drug permeated within 8 h through the goat nasal mucosa in ex vivo permeation studies. In pharmacokinetic studies, the Cmax in the brain following a single nasal administration of ESCI-loaded CSNPs in situ gel was 4.67 folds higher than the oral solution. The total AUC0-12in situ gel was 3.40 times higher than the i. n drug solution and 13.31 times higher than an oral solution. The mean residence time (MRT) for the brain’s CSNPs in situ gel was higher than i. n drug and oral solutions.Conclusion: This higher Cmax and prolonged MRT in the brain highlight the potential of CSNPs in situ gel as an effective brain-targeting system via the intranasal route. These results indicate that i. n delivery of the ESCl-loaded CSNPs in situ gel is a promising strategy for controlled release of ESCI, enhancing therapeutic efficacy and mitigating the disadvantages of oral delivery.